Tragedy, the Greeks, and us - Critchley, Simon 1960- (Pantheon Books, 2019)
"From the curator of The New York Times's "The Stone," a provocative and timely exploration into tragedy...how it articulates conflicts and contradiction that we need to address in order to better understand the world we live in. We might think we are through with the past, but the past isn't through with us. Tragedy permits us to come face to face with what we do not know about ourselves but that which makes those selves who we are. Having Been Born is a compelling examination of ancient Greek origins in the development and history of tragedy...a story that represents what we thought we knew about the poets, dramatists, and philosophers of ancient Greece...and shows them to us in an unfamiliar, unexpected, and original light"...